Rekonstruksi Epistemologi Manajemen Pendidikan Islam di Era Kecerdasan Artifisial - Arini Zahwatul Khoiroh; Hotimah, Husnul; Rohmah, Yulia Thibatur; Mardiyah, Mardiyah (Jurnal Kependidikan Islam, 2023)
Digital technology and artificial intelligence (AI) create an epistemological dilemma in Islamic educational management: the risk of becoming technocratic by relying solely on algorithmic efficiency, or unresponsive if religious values serve merely as normative legitimation. This critical-integrative literature review aims to reconstruct the epistemological foundations of Islamic educational management by integrating revelation, rationality, empirical evidence, and ethics. The study proposes the Integrative-Trusteeship Epistemology Model, which comprises five dimensions: tawhidic-maqasid orientation, critical rationality, data validation, participatory deliberation, and ethical-digital accountability. This model is operationalized through a cycle of purpose, evidence, consultation, action, and muhasabah (reflective accountability). The novelty lies in shifting knowledge governance to position AI and data as supportive instruments rather than moral authorities. This framework ensures that innovation and leadership in Islamic educational institutions remain effective, humane, and responsible.